The Harary Index of All Unicyclic Graphs with Given Diameter - Bao-Hua Xing; Gui-Dong Yu; Li-Xiang Wang; Jinde Cao (Discrete Dynamics in Nature and Society)
The Harary index of G is the sum of reciprocals of distance between any two vertices in G. In this paper, we obtain the graphs with the maximum and second-maximum Harary indices among n-vertex unicyclic graphs with diameter d.